The design and implementation of an agent-based auction service. (6th March 2009) - Dobriceanu, Adriana; Biscu, Laurentiu; Badica, Amelia; Badica, Costin
In this paper, we present the architecture, design and implementation of an agent-based service for automated auctions. The presentation covers the conceptual architecture, types of agents, agent communication and design and implementation issues. The experimental results to assess the performance of the service in terms of latency and throughput as functions of the number of auction participants and number of simultaneously active auctions are also included. The results confirmed that while the solution allows an increased level of flexibility and reusability as compared with existing approaches, it still suffers from performance and scalability problems that we plan to address in the near future.